Tantangan Implementasi Good Corporate Governance dalam Manajemen Keuangan Syariah: Studi Kasus pada Lembaga Keuangan Syariah di Indonesia: Penelitian - Rinda Trihariyanto, Ranto; Kumaidi, Kumaidi; Mawardi, Mawardi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the challenges in implementing Good Corporate Governance (GCG) within Islamic financial management in Indonesia. The research employs a descriptive qualitative approach using in-depth interviews, observations, and document analysis from several Islamic Financial Institutions (IFIs). The findings reveal that although the principles of GCG—transparency, accountability, responsibility, independence, and fairness—have been applied, their implementation still faces various obstacles. The main challenges include limited human resources capable of integrating modern management with fiqh muamalah, weak supervision by the Sharia Supervisory Board (SSB), and overlapping regulations between conventional and Islamic systems. To address these issues, IFIs need to enhance human resource competencies, expand the strategic role of the SSB, and develop integrated digital-based compliance systems. This research highlights the importance of synergy between GCG principles and maqasid al-shariah values as the foundation for equitable and sustainable Islamic corporate governance.